Settlement Analysis of Saturated Tailings Dam Treated by CFG Pile Composite Foundation - Jinxing Lai; Houquan Liu; Junling Qiu; Jianxun Chen (Advances in Materials Science and Engineering)
Cement fly ash gravel (CFG) pile composite foundation is an effective and economic foundation treatment approach, which is significant to building foundation, subgrade construction, and so forth. The present paper aims at investigating the settlement behaviors of saturated tailings dam soft ground under CFG pile composite foundation treatment, in which FEM and laboratory model test were utilized. The proposed findings demonstrate that CFG pile treatment is effective in reinforcing saturated tailings dam and loading has little influence on settlement of soil between piles. The variation of soil between piles settlement in FEM has a good agreement with the laboratory model test. Additionally, the cushion deformation modulus has a small effect on the composite foundation settlement, although the cushion thickness will generate certain influence on the settlement distribution of the composite foundation.